Validation and Normative Data for the Spanish Version of Sniffin’s Sticks Olfactory Identification Test - Delgado-Losada , María Luisa; Bouhaben , Jaime; Delgado-Lima , Alice Helena (Current Innovations in Disease and Health Research Vol. 8, 2023)
The goal of this study is to translate the Sniffin' Sticks Olfactory Identification Test into Spanish and get normative values for the Spanish population, taking into account the characteristics of free recall and subjective odor intensity. 'Sniffin' Sticks' is a new test of nasal chemosensory performance based on pen-like odor dispensing devices. It comprises three tests of olfactory function, namely tests for odor threshold (n-butanol, testing by means of a single staircase), odor discrimination (16 pairs of odorants, triple forced choice) and odor identification (16 common odorants, multiple forced choice from four verbal items per test odorant). The influence of possible demographic covariates such as sex, age, smoking, or educational level are taken in consideration, and the items that best discriminate are studied. In addition, the internal structure validity of the blue and purple versions is studied as a parallel measure, and a cultural adaptation of the purple version is carried out and, three independent samples of normosmic healthy volunteers were studied. To obtain normative values, the sample was of 417 participants (18–89 years). For the internal structure validity study of both versions, the sample was 226 (18–70 years), and for familiarity of the purple version, the sample was 75 participants (21–79 years). Results indicated that men and women and smokers and non-smokers perform equally. However, significant differences were found as age progresses, being more pronounced after 60 years old in all three measurements of the identification test. This study provides normative data of the scores that make up the validation of the Spanish version of the identification test are free recall, recognition and intensity. This research also provides the items that best discriminate in the blue version and a cultural adaptation for the purple version. In summary, the Sniffin’ Sticks Odor Identification Test proves to be a fitting instrument for evaluating olfaction among the Spanish population. This tool has been enhanced with the incorporation of two additional scores, accompanied by normative data categorized by age. The parallel version of the test appears suitable for assessment, given the cultural adaptation of its items and the demonstrated internal structural validity for both versions.”